A controladoria no processo de gestão das operadoras de plano de assistência à saúde do sistema UNIMED - Lima, Ana Cristina Cavalcante (2010)
The globalization and increased market competitiveness to do companies must make their management more and more effective. The health sector also suffers the additional impact, in addition, the regulator of this sector requires excellence in its management process. The controllership appear in this context in order to help the company to achieve the excellence of this work is to analyze the functions of controllership the process of managing of the agencies of health care’s plan of the Sistema UNIMED. In developing this work, we performed a descriptive research, adopting as a research strategy the case study. Units of study include analysis of the 29 operators of large of the Sistema Unimed, as ranked by ANS. In the survey, we used a questionnaire with dichotomous choice questions, multiple choices and these, combined with some open questions for the managers themselves of controllership or managing a business, when the first does not exist. Survey results identified that most of the companies examined has the organ of controllership in its organizational structure, and like a organ line. The functions of the controllership raised in the literature review, most of which is practiced by companies surveyed. It was also found that operators surveyed the practice the controllership’s functions in the process of management, but not all functions are charged by the controllership.